PRESS RELEASE - COMPONENTS OF ENVIRONMENTAL TOBACCO SMOKE (ETS) CONFIRMED TO BE MINIMAL - ALMOST NON-EXISTENT IN NONSMOKING SECTIONS. NEWS RELEASE. (Tufts Archival Research Center, 2007)
Report by the Tobacco Institute regarding the risk of secondhand smoke to passengers and flight attendants on commercial flights. States that the risk is negligible and that the current precautions, separate sections for smokers and non-smokers, are enough to ensure everyone's safety. Suggests that better ventilation is needed instead of a ban on smoking.